Country Partnership Framework for the Republic of Armenia for the Period FY19-FY23 - World Bank Group (World Bank, Washington, DC, 2019)
The country partnership framework (CPF) for FY19-FY23 outlines a program of support to the Government of Armenia’s vision for a just, inclusive, and citizen-centric Armenia. The World Bank Group (WBG) strategy will capitalize on the new momentum for deeper reforms and commitment to good governance brought about by recent political changes in Armenia to support a rebalancing of the economy toward a new growth model. The CPF presents to focus on: (i) boosting export enablers and firm competitiveness; (ii) enhancing human capital and equity; and (iii) sustainably managing environmental and natural resources. The CPF will seek opportunities under each focus area to incorporate key elements of good governance and inclusion: public accountability and transparency, citizen engagement, gender equity, spatial equity, and digital connectivity. The CPF focus areas were informed by extensive stakeholder consultations with the government, development partners, the private sector, and civil society; by the development challenges and opportunities highlighted in the government program and the WBG’s systematic country diagnostic (SCD) for Armenia.